Chemical laboratory safety awareness, attitudes and practices of tertiary students. (July 2017) - Walters, Ayana U.C.; Lawrence, Wendy; Jalsa, Nigel K.
Highlights: Chemical laboratory safety awareness among tertiary students is deficient. Awareness was found to be high but in need of improvement. The use of safe practices was found to be weakly correlated to awareness. Further education and training should be incorporated into the curriculum. Abstract: This study investigated the current state of chemical laboratory safety awareness, attitudes and practices among tertiary students in Trinidad. It also sought to determine if there was any correlation between awareness and practice and if there were any useful predictors for the likelihood of accidents in the laboratory. The cross-sectional survey was conducted at three institutions with a sample size of 226 students. A self-administered questionnaire was used to collect data which were analysed using descriptive statistics, the Pearson correlation coefficient, and binary logistic regression. Additionally, a semi-structured interview was conducted with a member of the supervisory staff at each institution to gain insight into the established safety procedures. The results show that though awareness was high there were deficiencies in the areas of hazard identification and emergency response. Attitudes and practices were acceptable but needed improvement, with a weak correlation existing between these two variables. The characteristics of the particular institution were found to be the only predictor of the likelihood of accidents. It was concluded that more education and training need to be implemented for improvement.